E-dopt: A Mobile Application for Pet Adoption in Indonesia - Santy Santy; Ryan Karuna; Alvin Budiman (Universitas Ahmad Dahlan, 2018)
In this research, we discuss the current trend on pet adoption in Indonesia and introduce a mobile application called e-dopt to encourage more pet adoption in Indonesia. Pet adoption mobile application is not yet popular in Indonesia, thus the benefit of conducting this research. Within this research, a mobile application to help the pet adoption process has been developed. The mobile application is developed on Android platform and the requirements are gathered by interviews, surveys, and research that have been conducted. The mobile application developed provides convenience for those who wants to adopt or give out pets and also allows businesses in pet product industry to use the mobile application as a sales channel.